The Gut Microbiome as a Target for the Treatment of Type 2 Diabetes - Aydin, Ömrüm (Curr Diab Rep, 2018)
PURPOSE OF REVIEW: The objective of this review is to critically assess the contributing role of the gut microbiota in human obesity and type 2 diabetes (T2D). RECENT FINDINGS: Experiments in animal and human studies have produced growing evidence for the causality of the gut microbiome in developing obesity and T2D. The introduction of high-throughput sequencing technologies has provided novel insight into the interpersonal differences in microbiome composition and function. SUMMARY: The intestinal microbiota is known to be associated with metabolic syndrome and related comorbidities. Associated diseases including obesity, T2D, and fatty liver disease (NAFLD/NASH) all seem to be linked to altered microbial composition; however, causality has not been proven yet. Elucidating the potential causal and personalized role of the human gut microbiota in obesity and T2D is highly prioritized.